Mechanical Thrombectomy in Acute Ischemic Stroke Patients Performed Within and Outside Clinical Trials in the United States. Issue 7 (16th November 2020) - Qureshi, Adnan I; Singh, Baljinder; Huang, Wei; Du, Zhiyuan; Lobanova, Iryna; Liaqat, Jahanzeb; Siddiq, Farhan
Graphical Abstract: